Development of the Parent Perceptions of Physical Activity Scale (PPPAS): Results from two studies with parents of infants and toddlers - Lakes, Kimberley D.; Vaughan, Jessica; Radom-Aizik, Shlomit; Taylor Lucas, Candice; Stehli, Annamarie; Cooper, Dan (PloS one, 2019)
Physical activity (PA) is important from birth to promote health and motor development. Parents of young children are gatekeepers of opportunities for PA, yet little is known about their perceptions of PA. We describe the development of the Parent Perceptions of Physical Activity Scale (PPPAS) across two studies (N = 241 parents). In Study 1, 143 parents of infants and toddlers recruited from neonatal intensive care units (NICUs) and childcare centers completed a 48-item PPPAS. In Study 2, 98 parents of premature infants completed the revised 34-item PPPAS. Study 1 principal components analysis (PCA) identified three components (benefits of, barriers to, and perceived influence on PA), and the scale was reduced. Scores for Perceived Barriers to PA were significantly different between groups, U = 1,108, z = -4.777, p < .0001, with NICU parents reporting more barriers to PA than childcare parents. In Study 2, PCA revealed the same components, and the scale was further reduced to 25 items. Three subscales measuring perceived benefits of, barriers to, and influence over an infant's PA produced Cronbach's alphas of .93, .85, .81, respectively. Results demonstrated sufficient construct validity and internal consistency of PPPAS scores, supporting its use in future PA research.